CRANIOMETRY OF THE FACIAL PART OF THE SKULL - Елена Александровна Киселева; Ольга Павловна Иванова; Сергей Владимирович Черненко; Ольга Сергеевна Корчемная; Владимир Маркович Корчемный; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
This article is devoted to the problem of studying the connections of the maxillary system with other parts of the face and skull using computer tomography.